Impact of modern technology on the development of natural-based products - Ariffin, Siti Fariza; Al-Shami, Abdulkareem Mohammed; Syed Omar, Sharifah Shakirah; Abdul Jalil, Mohd Azri; Khalid, Kamarul Ariffin; Ab. Hadi, Hazrina (Journal of Ayurvedic and Herbal Medicine (JAHM), 2019)
Advanced drug delivery systems such as liposomes, niosomes, ethosomes and phytosomes significantly influence the quality of synthetic drug formulations. However, the trend is now shifting towards natural-based moieties, most probably because of their promising therapeutic responses, and considerably lower incidence of side effects and toxicity issues. The effectiveness of herbal plant formulations in nano-sized particles in the delivery of active compounds is increased since nanoparticles offer a larger surface area and promote longer contact time with the surfaces of the targeted sites. Thus, nanoparticles allow the sustained release of small amounts of active compounds and the optimization of the dosing frequency of the drug. The implementation of nanotechnology in the development of natural-based products is able to enhance the delivery of plant extracts and active phytochemicals to the targeted sites. In fact, maximum therapeutic outcomes can be achieved since the herbal formulations are more stable compared to traditional preparations. The development of herbal formulations in modern drug delivery systems will be further discussed in this review. The possible improvement of phytosomes is highlighted in order to give future insights into improvising phytosomes as a targeted drug carrier system. A compilation of evidence-based studies involving the nanotechnology of herbal formulations is summarized accordingly. The use of modern technology in herbal drug delivery systems has been growing in past decades and needs to be further explored by scientists. Hence, at the end of this review, a brief summary is given of a few success stories regarding modern nano formulations that have been commercialized by leading herbal companies and which can be considered as great achievements in this field. Thus, this review is aimed at exploring the use of nanotechnology in drug delivery systems and discusses their contribution to the design of modern herbal formulations.